Comparison of pulsed vacuum and ultrasound osmotic dehydration on drying of Chinese ginger (Zingiber officinale Roscoe): Drying characteristics, antioxidant capacity, and volatile profiles. Issue 8 (28th June 2019) - An, Kejing; Tang, Daobang; Wu, Jijun; Fu, Manqin; Wen, Jing; Xiao, Gengsheng; Xu, Yujuan
Abstract: The effects of pulsed vacuum osmotic dehydration (PVOD) and ultrasound osmotic dehydration (USOD) on drying characteristics and quality attributes of ginger were investigated. PVOD was subjected to pulsed vacuum at 13 kPa for 30 min, and USOD was subjected to ultrasound with the frequency of 40 kHz for 30 min. After PVOD and USOD treatments, the samples were then dried at intermittent microwave & air‐drying oven with an output of 700 W and temperature of 60°C to the final moisture content of 0.12 g water/g d.w. The results showed PVOD and USOD treatments could improve the total phenolic contents by −1.8% to 16.4%, total flavonoid content by 7.7%–18.7%, DPPH radical scavenging by 9.5%–12.2%, and ABTS+ antioxidant activity by 17.8%–27.4%, although they prolonged the later stages drying of ginger. Besides, the PVOD‐ and USOD‐pretreated dried samples had less brownings than the untreated‐dried samples which could be attributed to the inactivation of polyphenol oxidase (PPO) and peroxidase (POD). The PPO activity was significantly reduced in the PVOD and USOD ginger, whereas POD activity was decreased in USOD ginger but increased in PVOD ginger. Moreover, PVOD pretreatment also led to a better preservation of volatile profiles and cell structure than USOD treatment. Therefore, both PVOD and USOD are effective pretreatments for drying of ginger. Abstract : "Comparison of pulsed vacuum and ultrasound osmotic dehydration on drying of Chinese ginger ( Zingiber officinale Roscoe): drying characteristics, antioxidant capacity, and volatile profiles" by Yujuan Xu et al. Pulsed vacuum osmotic dehydration (PVOD) and ultrasound osmotic dehydration (USOD) significantly inhibited enzymatic brownings and increased total flavonoid content, DPPH radical scavenging, and ABTS+ antioxidant activity of dried ginger. PVOD treatment conserved volatile profiles and preserved cell structure more effectively than did USOD treatment. As pretreated dried ginger was higher quality than the untreated‐dried ginger, PVOD and USOD are both effective pretreatments for drying of ginger.